Applications of nanotechnologies for miRNA-based cancer therapeutics: current advances and future perspectives - Bravo-Vázquez, Luis Alberto; Méndez-García, Andrea; Rodríguez, Alma L.; Sahare, Padmavati; Pathak, Surajit; Banerjee, Antara; Duttaroy, Asim K.; Paul, Sujay (Frontiers in Bioengineering and Biotechnology, 2023)
MicroRNAs (miRNAs) are short (18-25 nt), non-coding, widely conserved RNA molecules responsible for regulating gene expression via sequence-specific post-transcriptional mechanisms. Since the human miRNA transcriptome regulates the expression of a number of tumor suppressors and oncogenes, its dysregulation is associated with the clinical onset of different types of cancer. Despite the fact that numerous therapeutic approaches have been designed in recent years to treat cancer, the complexity of the disease manifested by each patient has prevented the development of a highly effective disease management strategy.However, over the past decade, artificial miRNAs (i.e., anti-miRNAs and miRNA mimics) have shown promising results against various cancer types; however, their targeted delivery could be challenging. Notably, numerous reports have shown that nanotechnology-based delivery of miRNAs can greatly contribute to hindering cancer initiation and development processes, representing an innovative disease-modifying strategy against cancer. Hence, in this review, we evaluate recently developed nanotechnology-based miRNA drug delivery systems for cancer therapeutics and discuss the potential challenges and future directions, such as the promising use of plant-made nanoparticles, phytochemical-mediated modulation of miRNAs, and nanozymes.